LEXICAL COHESION IN KOMPAS.COM ARTICLES AS A RESOURCE FOR TEACHING DESCRIPTIVE WRITING TO NINTH-GRADE STUDENTS (International Journal of Cultural and Social Science, 2026)
This study aims to describe lexical cohesion in Kompas.com articles and its relevance as a resource for teaching descriptive writing to ninth-grade students. This research employed a descriptive qualitative approach. The data were collected from 20 Kompas.com articles published in September–October 2025 and analyzed using content analysis. The findings revealed 260 instances of lexical cohesion, consisting of collocation (65), hyponymy (64), repetition (60), synonymy (46), and antonymy (25). Collocation was the most dominant type, while antonymy was the least frequent. These findings indicate that Kompas.com articles provide varied, authentic, and contextual examples of lexical cohesion. They can be used as supplementary learning resources for identifying cohesion patterns, enriching vocabulary, reducing unnecessary repetition, and developing coherent descriptive paragraphs.